Contemporary Lingvodidactics: Defining Goals and Objectives of Foreign Language Teaching - T. K Tsvetkova (Vestnik MGIMO-Universiteta, 2013)
The author suggests her own interpretation of goals and objectives of foreign language teaching based on the author’s original conception of mastering a foreign language as a process of bilingual development. The final goal should be described not as a set of competencies, but as a form of bilingualism. Intermediate goals and objectives should be determined by the task of developing each block of the mechanism of language command.